2011 International Conference on Electronics, Communications and Control (ICECC) 2011
DOI: 10.1109/icecc.2011.6068034
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chlorpyrifos on microbial respiration and enzyme activities in soil

Abstract: To investigate the effects of different concentrations of chlorpyrifos on soil ecological environment and on soil respiration, catalase, urease, and levansucrase activity, studied by laboratory simulation methods. The results showed that: different concentrations of chlorpyrifos on soil respiration has a significant activation effect only at the first day, and a positive correlation with the concentration; different concentrations of chlorpyrifos on soil catalase activity is not significant; the inhibition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…to application of chlorothalonil herbicide. Similarly, Niu et al (2011) reported an inhibition in urease activity due to high dose of chlorpyriphos. All sites showed considerable decreases in dehydrogenase activity in soil X as compared to soil Y.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…to application of chlorothalonil herbicide. Similarly, Niu et al (2011) reported an inhibition in urease activity due to high dose of chlorpyriphos. All sites showed considerable decreases in dehydrogenase activity in soil X as compared to soil Y.…”
Section: Discussionmentioning
confidence: 95%
“…Soil phosphatases promote mineralization of organic phosphorus and enhance its availability to soil microorganisms and plants (Schneider et al 2001). Niu et al (2011) observed a considerable decline in urease activity due to high concentration of chlorpyriphos (100 and 500 mg kg −1 ) as compared to low concentration (10 mg kg -1 ). Pampulha and Oliveira (2006) found 74% inhibition in dehydrogenase activity by 1.0 mg kg -1 dose of the combined mixture of bromoxynil + prosulfuron as compared to control.…”
Section: Introductionmentioning
confidence: 98%